Mines in use in multinational operations - Kovačević, Nenad V. (Vojnotehnički glasnik / Military Technical Courier, 2016)
Members of the Ministry of Defence (MoD) and the Serbian Armed Forces (SAF) have been engaged in multinational operations (MnOPs) from 26 June 2002. During the engagement in UN MnOPs, one of the key problems is the procedures when encountering some kind of ordnance. During the preparation of MoD and SAF members for joining UN MNOPs, one of the main problems is a small number of qualified and trained instructors as well as the lack of necessary literature. The paper presents a summary review of one ordnance type - mines, i.e. a review of the most typical representatives of mine types that can be found in some of the territories where MnOPs are conducted. In order to prevent mine accidents, particular attention must be paid to the training i.e. preparation of MoD and SAF members for their participation in MnOPs. The work is primarily based on the currently available literature as well as on the experiences of MoD and SAF members who were engaged in UN MnOPs.